Occipital Neuralgia after Hair Transplantation and Its Treatment - Jason Siefferman; Yury Khelemsky (Case Reports in Neurological Medicine)
While undergoing full thickness tissue harvest from the posterior scalp, a 72-year-old man experienced immediate severe pain in the right occiput and was unable to complete the procedure. The pain was constant “sharp” and “shocking” with numbness in the distribution of the lesser occipital nerve, exacerbated by physical activity, and local anesthetic blocks provided temporary complete relief. After numerous treatments over several years, including oral analgesics, botulinum toxin injections, and acupuncture, proved ineffective, pulsed radiofrequency neuromodulation provided greater than 80% relief for 5 months.